Ansiedade pré-operatória em pacientes cirúrgicos hospitalizados de Goiânia-Go - Melchior, Lorena Morena Rosa (2017)
INTRODUCTION: The anesthetic-surgical procedure is a complex and critical process, a moment that can generate important implications for the patients, and can generate diverse feelings such as anxiety and fear. Preoperative anxiety has affected about 60 to 80% of surgical patients. The patient's emotionally unstable surgery is scary and traumatic and is still predisposed to complications. PURPOSE: To investigate the profile of anxious patients hospitalized in preoperative elective surgery. METHOD: A cross-sectional, analytical study with subsequent cohort formation, performed at a public university hospital in the city of Goiânia-GO, Brazil. The population consisted of preoperative elective surgery patients hospitalized in surgical units, the sample was constituted of 200 patients in the preoperative period, by means of a sample calculation. Four instruments were used, one structured with sociodemographic and clinical-surgical questions; The Hamilton anxiety scale; The numerical scale of pain and the admission card of the surgical center. The study was carried out in total accordance with the Resolution 466/2012 regarding ethical issues. The analysis was expressed in absolute and relative frequencies and the Chi-square test was employed, with a significance level of 5%. The Prevalence Ratio (PR) was evaluated through gross and adjusted Poisson regression. RESULTS: The prevalence of anxiety was 53,0% (n=106) (CI 95% 46,06/59,85), mild anxiety was present in 67,0% (n=71) (CI 95%; 57,6-75,4), and 33,0% (n=35) (CI 95% 24,5/42,3) of the patients presented moderate and severe anxiety. In the multivariate analysis, sex, occupation and fear of anesthesia were significant, configuring as predictors to moderate and severe anxiety. The fear of anesthesia, of something going wrong, or of dying emerged in a predominant part of the sample, and the fear of errors showed significant relation to moderate and severe anxiety. CONCLUSIONS: The prevalence of preoperative anxiety found in the study was high. Most of the anxious patients expressed levels of mild anxiety. The most common factors that led to anxiety were the fear of death and of errors by the surgical team. Sex, occupation and fear of anesthesia configured as predictors to moderate and severe anxiety.